Case reportScleromyxedema: a rare disorder and its treatment difficulties - Koleta Koronowska, Sandra; Osmola-Mańkowska, Agnieszka; Jakubowicz, Oliwia; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Scleromyxedema is a rare progressive cutaneous mucinosis, usually associated with a systemic involvement and paraproteinemia. Its aetiology remains unknown. The therapeutic options include numerous treatment modalities, however, no standard treatment exists as the rarity of this disease prevents the execution of controlled therapeutic trials. This paper reports a case of a 38-year-old male with progressive scleromyxedema associated with gammopathy. Initially, the patient was treated with prednisolone and later etretinate was added to the therapeutic schedule with quite good clinical improvement. However, after 6 months of treatment, several adverse effects were observed: hypercholesterolemia, hypertriglyceridaemia and cataract of the right eye. The patient was consulted by dermatologists in Warsaw and Gdansk as well as by a haematologist. The patient was excluded from oncological treatment. Melphalan therapy was not recommended as it is associated with very toxic side effects. IVIG treatment (intravenous immunoglobulin) was not initiated because of financial issues. As the disease progressed, treatment with plasmapheresis was introduced. The patient received 4 cycles of the therapy. It was well-tolerated by the patient and gave satisfactory, but temporary results. In order to obtain long-lasting improvement the patient was treated with IVIG (21.0 g/dose for 5 consecutive days). This treatment modality seems to have resulted in a more stable improvement.